MODERN REINDEER AND MICE: REVISED PHOSPHATE-WATER ISOTOPE EQUATIONS - Longinelli A.; Iacumin P.; Davanzo S.; Nikolaev V. (My University, 2003)
The oxygen isotope composition of bone and tooth phosphate of 34 mice specimens (Pitymus sp., Microtus arvalis and Arvicola terrestris) coming from seven different locations in Italy, Germany and Switzerland was measured by means of well-established techniques. These measurements were carried out with the purpose of establishing quantitative relationships between the δ18Op from different mice genera and the mean δ18Ow values and to compare these data to previous measurements carried out on various specimens belonging to the genus Apodemus. The three genera studied showed a similar behaviour when compared to the mean δ18Ow values. The slope of the equation calculated for these three genera is significantly different from the slope obtained from Apodemus specimens. Reconsidering the δ18Ow values suggested in the case of Apodemus due to the small number of data available at that time, it seems that these values are too negative by 0.5 to about 1.5‰. If so, the Apodemus equation becomes almost identical to the equation calculated for the new mice values and, consequently, one could conclude that several micromammal genera and species might behave in the same way and obey the same relationship with the mean δ18Ow values. A set of 25 samples of modern reindeer skeletal material from Spitzbergen, Russia and Siberia was also studied with the aim of improving the reindeer isotope equation obtained from a previous study. In fact, the slope of that equation was somehow uncertain due to a rather large range of isotope values obtained from each group of reindeers coming from the same location. The new results confirm such ‘anomalous’ behaviour already shown by other mammals and probably related to dietary behaviours, water fluxes with the environment and isotopic composition of ingested food and water rather than to imperfect equilibrium conditions with environmental water. However, the equation calculated from both the old and new, statistically more significant, isotope results is not far from the previous one.